The silent revolution: an introduction to gene regulation by microRNAs - Slack, Frank (Henry Stewart Talks, 2007)
miRNAs as endogenous small RNA regulators, Biogenesis of miRNAs, miRNAs and siRNAs, Mechanism of action of miRNAs, Targets of miRNAs, Biological roles for miRNAs, Roles for miRNAs in cancer
Reviewed at 2017/02/06